Novel setup for rapid phase contrast CT imaging of heavy and bulky specimens - Dullin, Christian; D'Amico, Lorenzo; Saccomano, Giulia; Longo, Elena; Wagner, Willi Linus; Reiser, Johanna; Svetlove, Angelika; Albers, Jonas; Contillo, Adriano; Abrami, Alessandro; Sturari, Luca; Tromba, Giuliana; et al. (Journal of synchrotron radiation, 2023)
This work introduces a novel setup for computed tomography of heavy and bulky specimens at the SYRMEP beamline of the Italian synchrotron Elettra. All the key features of the setup are described and the first application to off-center computed tomography scanning of a human chest phantom (approximately 45 kg) as well as the first results for vertical helical acquisitions are discussed.
Gesehen am 14.06.2023